2008
DOI: 10.1519/jsc.0b013e318181ac20
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Physical Fitness Test Results and Hockey Playing Potential in Elite-Level Ice Hockey Players

Abstract: The primary purpose of this study was to determine the fitness variables with the highest capability for predicting hockey playing potential at the elite level as determined by entry draft selection order. We also examined the differences associated with the predictive abilities of the test components among playing positions. The secondary purpose of this study was to update the physiological profile of contemporary hockey players including positional differences. Fitness test results conducted by our laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
137
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(150 citation statements)
references
References 4 publications
10
137
1
2
Order By: Relevance
“…It appears that the men in the current study (Table 2) had a relative aerobic capacity (VO 2peak 56 ml · kg -1 · min -1 ) comparable to previous findings. A study of the players in the NHL entry draft (graded cycle ergometer test) reported an aerobic capacity of 58.1 and 56.7 ml · kg -1 · min -1 for forwards and defensive players respectively (6), and a study from collegiate athletic ice hockey (graded treadmill test) reported an aerobic capacity of 59 ml · kg -1 · min -1 (17).…”
Section: Aerobic Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that the men in the current study (Table 2) had a relative aerobic capacity (VO 2peak 56 ml · kg -1 · min -1 ) comparable to previous findings. A study of the players in the NHL entry draft (graded cycle ergometer test) reported an aerobic capacity of 58.1 and 56.7 ml · kg -1 · min -1 for forwards and defensive players respectively (6), and a study from collegiate athletic ice hockey (graded treadmill test) reported an aerobic capacity of 59 ml · kg -1 · min -1 (17).…”
Section: Aerobic Capacitymentioning
confidence: 99%
“…Off-ice physiological fitness in men's ice hockey players has been studied before (1,3,(6)(7)(8)(9)(10) and the physiological profile has changed over the years as the players of today are taller and more physically fit, but with an unchanged body composition (1,7). Recent research has studied the physiological profiles of women's ice hockey players as well (11)(12)(13) On-ice tests for ice hockey players may measure physiologic fitness as well as skill, depending on the structure of test (3).…”
Section: Introductionmentioning
confidence: 99%
“…Standardized fitness testing protocols performed according to Burr et al, [37] were used to assess all fitness parameters used in this study. A 30-sec modified Wingate test performed on the Monark 834E Wingate ergometer was used to assess anaerobic performance, while aerobic power (VO 2 max) was assessed on the Monark 828 cycle ergometer ( Table 1a).…”
Section: Fitness Testingmentioning
confidence: 99%
“…It is difficult to compare our results with others, because there is a great variation among studies in used off-ice tests (Mascaro et al, 1992;Geithner et al, 2006;Burr et al, 2008;Ransdell & Murray, 2011;Ransdell et al, 2013;Henriksson et al, 2015). Moreover, above mentioned studies are conducted predominantly in elite women ice hockey players.…”
Section: Discussionmentioning
confidence: 83%